MENENTUKAN FPB DAN KPK MENGGUNAKAN TABEL PEMBAGIAN (PENGAJARAN MATEMATIKA SEKOLAH DASAR DAN MENENGAH) - Suprapto, Suprapto (Jurnal Ilmiah AdMathEdu, 2011)
The purposes of this paper are determined of gcd (greatest common divisor) and lcm (least common multiple) using division table. Namely: pair number (two or more numbers) is included in the columns on the first line. Then do the division with the least prime number of form rows in the table. The division will stop if the pair number cannot be common divided (or the numbers are relatively primes). Numbers which cannot be common divided the rest of the division. The determine gcd is equal to multiple of all the numbers in the first column. And the determining lcm is equal to multiple all numbers in the first column and last row.